Extragalactic radio surveys in the pre-Square Kilometre Array era. Issue 7 (19th July 2017) - Simpson, Chris
Abstract : The era of the Square Kilometre Array is almost upon us, and pathfinder telescopes are already in operation. This brief review summarizes our current knowledge of extragalactic radio sources, accumulated through six decades of continuum surveys at the low-frequency end of the electromagnetic spectrum and the extensive complementary observations at other wavelengths necessary to gain this understanding. The relationships between radio survey data and surveys at other wavelengths are discussed. Some of the outstanding questions are identified and prospects over the next few years are outlined.